Fatty acid magnesium salt particles and cosmetics
Fatty acid magnesium salt particles with controlled aspect ratios and particle distributions address the usability issues of conventional metal soaps, resulting in improved cosmetic performance through enhanced smoothness, glossiness, and transparency.
Patent Information
- Application Number
- JP2020164351
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-09-30
AI Technical Summary
Conventional metal soaps used in cosmetics lack improvements in terms of usability, particularly in achieving optimal aspect ratios and particle distributions for enhanced skin application and cosmetic performance.
Fatty acid magnesium salt particles with a specific aspect ratio of 1.0 or less, median diameter of 10.0 μm to 40.0 μm, and a particle size summary value of 2.5 or less, produced through a controlled double-solution reaction process, ensuring uniformity and stability.
The fatty acid magnesium salt particles provide improved smoothness, glossiness, and transparency in cosmetics, enhancing the overall usability and application experience.
Smart Images

Figure 0007623119000003 
Figure 0007623119000004 
Figure 0007623119000005
Abstract
Description
[Technical field]
[0001] The present invention relates to novel fatty acid magnesium salt particles and a cosmetic preparation containing the fatty acid magnesium salt particles. [Background technology]
[0002] Fatty acid magnesium salts are a type of metal soap that are useful as cosmetic additives, and have been used to improve the lubricity and adhesion to the skin, as dispersants for pigments, and for other purposes. Patent Document 1 describes a fatty acid magnesium salt having 6 to 24 carbon atoms obtained by a metathesis method, which does not exhibit an alkaline pH when dispersed in water. Patent Document 2 describes that by combining metal soap microparticles having a specific particle size with a partially crosslinked organopolysiloxane polymer, a solid powder cosmetic preparation that is excellent in usability, moldability, and impact resistance can be obtained. Patent Document 3 describes that by using a specific amount of metal soap fine particles having a specific particle size, a solid powder cosmetic preparation that is excellent in moldability, impact resistance, durability, etc. can be obtained. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2007-186463 A [Patent Document 2] JP 2018-168145 A [Patent Document 3] JP 2000-169342 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the above-mentioned conventional metal soaps have room for improvement in terms of usability. An object of the present invention is to provide a novel metal soap and cosmetic which are excellent in usability. [Means for solving the problem]
[0005] Means for Solving the Problems The present inventors have conducted extensive research to solve the above problems and have found that fatty acid magnesium salt particles having an aspect ratio within a specific range are excellent in usability. That is, the present invention relates to the following fatty acid magnesium salt particles and cosmetic preparation. [1] Fatty acid magnesium salt particles having an aspect ratio represented by the following formula (1) of 1.0 or more and 2.0 or less, wherein the fatty acid has a carbon number of 12 to 22, and the average thickness of the fatty acid magnesium salt particles is 250 to 600 nm. Aspect ratio = long axis diameter of particle (μm) / short axis diameter of particle (μm) Equation (1) [2] The fatty acid magnesium salt particles according to [1], having a median diameter of 10.0 μm to 40.0 μm. [3] The fatty acid magnesium salt particles according to [1] or [2], wherein the particle size summary value (A) represented by the following formula (3) satisfies the relationship of A≦2.5. Grain size summary value A = (D90 - D10) / D50... formula (3) (However, 10.0≦D50≦40.0) D10: 10% cumulative diameter (μm) of fatty acid magnesium salt particles on a volume basis D50: Median diameter of fatty acid magnesium salt particles on a volume basis (μm) D90: 90% cumulative diameter (μm) of fatty acid magnesium salt particles on a volume basis [4] The fatty acid magnesium salt particles according to any one of [1] to [3], wherein the fatty acid having 12 to 22 carbon atoms is myristic acid. [5] A cosmetic preparation comprising the fatty acid magnesium salt particles according to any one of [1] to [4]. Effect of the Invention
[0006] According to the present invention, fatty acid magnesium salt particles having excellent usability can be provided. Furthermore, according to the present invention, by containing the fatty acid magnesium salt particles, a cosmetic preparation having excellent usability can be provided. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a graph showing heat absorption by differential scanning calorimetry (DSC) of magnesium myristate. [Diagram 2] FIG. 2 is a photograph of the magnesium myristate of Example 1 observed with a scanning electron microscope. [Diagram 3] FIG. 3 is a photograph of the magnesium myristate of Example 3 observed with a scanning electron microscope. [Figure 4] FIG. 4 is a photograph of the magnesium myristate of Comparative Example 1 observed with a scanning electron microscope. [Diagram 5] FIG. 5 is a photograph of the magnesium myristate of Comparative Example 2 observed with a scanning electron microscope. [Figure 6] FIG. 6 is a photograph of the magnesium myristate of Comparative Example 3 observed with a scanning electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention will now be described in further detail. The fatty acid magnesium salt particles of the present invention are composed of a divalent fatty acid magnesium salt having 12 to 22 carbon atoms. Such particles can be prepared by a double decomposition method in which a fatty acid alkali compound salt obtained by reacting a fatty acid having 12 to 22 carbon atoms with a monovalent alkali compound is reacted with a divalent magnesium salt in an aqueous solution.
[0009] The fatty acid as the raw material of the fatty acid alkali compound salt is not particularly limited as long as it is a fatty acid having 12 to 22 carbon atoms. That is, it may be either a naturally derived fatty acid or a synthetic fatty acid, either a saturated fatty acid or an unsaturated fatty acid, and either a straight-chain or a branched fatty acid. Furthermore, the fatty acid structure may contain functional groups such as a hydroxyl group, an aldehyde group, and an epoxy group. As the fatty acid, a straight-chain saturated fatty acid is preferable.
[0010] In addition, when the carbon number of the fatty acid is 12 or more, it is possible to impart excellent usability to the cosmetic preparation. On the other hand, when the carbon number is 22 or less, it is easy to obtain the fatty acid industrially, and the solubility in water of the obtained fatty acid alkali compound salt is not significantly reduced, so that the productivity is high. The carbon number of the fatty acid is preferably 12 to 18, and more preferably 14 (i.e., the fatty acid magnesium is magnesium myristate).
[0011] Examples of fatty acids include lauric acid, myristic acid, myristoleic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, linoleic acid, arachic acid, behenic acid, erucic acid, hydroxystearic acid, and epoxystearic acid, among which myristic acid is preferred. When mixed fatty acids are used, the myristic acid content in the fatty acids is preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more.
[0012] Examples of monovalent alkali compounds that can be used as raw materials for fatty acid alkali compound salts include hydroxides of alkali metals (sodium, potassium, etc.), and amines such as ammonia, monoethanolamine, diethanolamine, triethanolamine, etc. Preferred are hydroxides of alkali metals such as sodium and potassium, because they have high solubility in water when made into fatty acid alkali compound salts.
[0013] The fatty acid alkali compound salt used in the present invention is obtained by reacting a monovalent alkali compound with a fatty acid at a temperature that is generally equal to or higher than the melting point of the fatty acid and at a temperature at which the fatty acid does not decompose, preferably 100°C or lower, more preferably 50 to 100°C, even more preferably 60 to 95°C, and particularly preferably 80 to 95°C.
[0014] The fatty acid magnesium salt particles of the present invention can be obtained, for example, by reacting the fatty acid alkali compound salt obtained above with a magnesium salt in an aqueous solution. The magnesium salt is specifically a salt of inorganic magnesium with an inorganic acid or an organic acid. Examples of the magnesium salt include magnesium chloride, magnesium sulfate, and magnesium acetate. In particular, magnesium chloride and sulfate are preferred because they have high solubility in water and react efficiently with the fatty acid alkali compound salt.
[0015] The reaction between the fatty acid alkali compound salt and the divalent magnesium salt is specifically carried out by separately preparing an aqueous solution containing the magnesium salt and an aqueous solution containing the fatty acid alkali compound salt, and then mixing them together, for example by adding the aqueous solution containing the magnesium salt to the aqueous solution containing the fatty acid alkali compound salt, or by adding both to separate reaction vessels.
[0016] When mixing the aqueous solution containing the fatty acid alkali compound salt with the aqueous solution containing the magnesium salt, for example, if the aqueous solution containing the magnesium salt is added to the aqueous solution containing the fatty acid alkali compound salt all at once, the shape of the resulting fatty acid magnesium salt particles may become non-uniform, and the aspect ratio of the particles may become large. Therefore, in the present invention, it is preferable to gradually drop the aqueous solution containing the magnesium salt into the aqueous solution containing the fatty acid alkali compound salt at an appropriate speed.
[0017] The concentration of the fatty acid alkali compound salt during the production of the fatty acid magnesium salt is usually 1% by mass to 20% by mass, preferably 5% by mass to 15% by mass, from the viewpoint of the productivity of the fatty acid magnesium salt and the handling properties of the fatty acid alkali compound salt-containing aqueous solution or the fatty acid magnesium salt slurry obtained. If the concentration of the fatty acid alkali compound salt is 1% by mass or more, the productivity of the fatty acid magnesium salt is good, which is preferable. If it is 20% by mass or less, the viscosity of the fatty acid alkali compound salt-containing aqueous solution or the fatty acid magnesium salt slurry obtained does not increase, and a uniform reaction can be performed. The concentration of the magnesium salt in the magnesium salt-containing liquid is usually 10% by mass to 50% by mass, preferably 10% by mass to 40% by mass, from the viewpoint of the productivity of the fatty acid magnesium salt and the handling properties of the fatty acid alkali compound salt-containing aqueous solution or the fatty acid magnesium salt slurry obtained.
[0018] The reaction between the fatty acid alkali compound salt and the magnesium salt is carried out under temperature conditions that are generally used by those skilled in the art, taking into consideration the solubility of the fatty acid alkali compound salt, preferably 50 to 100° C., more preferably 60 to 95° C. If the reaction temperature is 50° C. or higher, the reaction rate between the fatty acid alkali compound salt and the magnesium salt is good.
[0019] In order to stabilize the fatty acid magnesium salt slurry during the reaction of the fatty acid alkali compound salt with the magnesium salt and improve the productivity of the fatty acid magnesium salt, it is preferable to make a polyalkylene glycol ether, particularly a triblock ether having a structure (EO-PO-EO) in which an oxypropylene block is sandwiched between oxyethylene blocks, present in the fatty acid magnesium salt slurry. The content of the polyalkylene glycol ether in the fatty acid magnesium salt slurry is usually 0.01 to 5 parts by mass, preferably 0.05 to 2 parts by mass, per 100 parts by mass of the fatty acid alkali compound salt. The polyalkylene glycol ether may be present in the reaction system before the monovalent alkali compound is reacted with the fatty acid, or may be present in the reaction system before the reaction of the fatty acid alkali compound with the magnesium salt.
[0020] By this method, a fatty acid magnesium salt cake with reduced moisture content is obtained by separation using a dehydrator, a filter press, etc. The fatty acid magnesium salt cake with reduced moisture content is dried using a rotary dryer, an airflow dryer, a ventilated tray dryer, a vacuum tray dryer, a spray dryer, a fluidized bed dryer, etc.
[0021] In the present invention, the fatty acid magnesium salt cake must be dried at (α-60)°C≦α≦(α-30)°C relative to the water vaporization peak top temperature (α°C) of the fatty acid magnesium salt produced. Here, the water vaporization peak top temperature refers to the top peak of the temperature range at which the residual water contained in the fatty acid magnesium salt that cannot be removed by the drying begins to desorb. For example, in the heat absorption graph of magnesium myristate by differential scanning calorimetry (DSC) in FIG. 1, the water vaporization peak top temperature is 102.1°C. The specific drying temperature varies depending on the type of fatty acid magnesium salt obtained, but for example, in the case of magnesium myristate, it is 72°C or lower. If the drying process is performed at a temperature higher than 72°C, fine particles will adhere to each other, and the thickness of the particles will tend to increase. On the other hand, if the drying process is performed at a temperature lower than 40°C, the drying property will decrease, and a large amount of water will tend to remain in the compound, which may result in a decrease in productivity.
[0022] The fatty acid magnesium salt particles of the present invention have an aspect ratio of 1.0 or more and 2.0 or less, preferably 1.0 or more and 1.6 or less, and more preferably 1.0 or more and 1.5 or less. In the present invention, the aspect ratio of a particle corresponds to the following formula (1), that is, the value obtained by dividing the major axis diameter of a fatty acid magnesium salt particle by the minor axis diameter (=major axis diameter / minor axis diameter). Aspect ratio = long axis diameter of particle (μm) / short axis diameter of particle (μm) Equation (1) The closer the aspect ratio is to 1.0, the closer the particle shape is to a square or a circle. The fatty acid magnesium salt particles of the present invention preferably have a shape close to a square. This improves the spreadability on the skin and provides excellent usability.
[0023] The "major axis diameter" of a particle is the length of the major axis of the particle, more specifically, the width of the particle where the distance between the two parallel lines sandwiching the particle is maximum. The "minor axis diameter" of a particle is the length of the minor axis of the particle, more specifically, the width of the particle measured along a straight line passing through the midpoint of the major axis and perpendicular to the major axis. The average thickness of a particle is the average value obtained by measuring the side length of 10 particles when the surface with the largest area of the fatty acid magnesium salt particles is the front. The average thickness of a particle is a value measured based on a two-dimensional projection image of the particle (more specifically, a SEM photograph).
[0024] Moreover, the fatty acid magnesium salt particles of the present invention have an average particle thickness of 250 to 600 nm. With such a thickness, the particles are easily dissolved even under mild mixing conditions (production method) in cosmetics, and the cosmetic can be easily applied uniformly to the skin, and the feel after application can be improved. Furthermore, when the average thickness is 250 nm or more, the fatty acid magnesium salt particles have good handleability when added to cosmetics, and there is no risk of a decrease in workability. The average particle thickness is more preferably 280 to 450 nm, and particularly preferably 300 to 450 nm. If the average particle thickness is 300 to 450 nm, the action and effect of the present invention can be obtained even more stably.
[0025] Furthermore, the fatty acid magnesium salt particles of the present invention preferably have a particle index of 1.5 or more and 8.0 or less. Such a particle index makes it easier to apply the fatty acid magnesium salt particles uniformly to the skin as a cosmetic, and the feeling after application can be maintained for a long time. Furthermore, if the particle index is 1.5 or more, the fatty acid magnesium salt particles have good dispersibility when added to a cosmetic, and there is no risk of a decrease in workability. The particle index of the particles is preferably 1.5 or more and 6.0 or less, and more preferably 2.0 or more and 5.0 or less. If the particle index is 2.0 or more and 5.0 or less, the effect of the present invention can be obtained even more stably. In the present invention, the particle index of a particle corresponds to the following formula (2), i.e., the value obtained by dividing the major axis diameter of a fatty acid magnesium salt particle by the minor axis diameter (=major axis diameter / minor axis diameter) by the average thickness of the particle [=(major axis diameter / minor axis diameter) / average thickness of the particle]. Particle index = [(major axis diameter of particle (μm) / minor axis diameter of particle (μm)) / average thickness of particle (nm)] × 1000 Equation (2)
[0026] Furthermore, the fatty acid magnesium salt particles of the present invention have a narrow particle size distribution, which allows them to be uniformly present in a cosmetic, and the effects of the present invention (particularly, improved feel of the cosmetic) are more likely to be exhibited stably. Specifically, the fatty acid magnesium salt particles preferably have a median diameter of 10.0 to 40.0 μm, and a particle size summary value A represented by the following formula (3) is preferably 2.5 or less. Grain size summary value A = (D90 - D10) / D50... formula (3) (However, 10.0≦D50≦40.0) D10: 10% cumulative diameter (μm) of fatty acid magnesium salt particles on a volume basis D50: Median diameter of fatty acid magnesium salt particles on a volume basis (μm) D90: 90% cumulative diameter (μm) of fatty acid magnesium salt particles on a volume basis
[0027] In the present invention, the particle size summary value A is calculated from the particle size measured by a microtrack laser diffraction method. When the particle size summary value A is 2.5 or less, the particle size of the fatty acid magnesium salt particles present in the cosmetic becomes uniform, the dispersibility of the cosmetic is good, the productivity does not decrease, and a cosmetic having the desired feel can be produced. It is more preferable that the particle size summary value A satisfies the relationship of 0.5≦A≦2.5. When the relationship of 0.5≦A≦2.5 is satisfied, the action and effect of the present invention can be obtained even more stably. When the particle size summary value A is 0.5 or more, the yield does not decrease and the production can be stably carried out on an industrial scale. In addition, when the cumulative curve is calculated by the above formula (3) with the total volume of the powder group being 100%, the particle diameters at the points where the cumulative curve is 10%, 50%, and 90% are the 10% cumulative diameter (D10), 50% median diameter (D50; median diameter), and 90% cumulative diameter (D90) (μm), respectively. Note that particle diameter means the particle diameter of the primary particle. If the particles are aggregated during measurement, they are measured in a dispersed state using ultrasound or the like.
[0028] The particle size summary value A can be adjusted by appropriately adjusting the concentration of the fatty acid alkali compound salt, the temperature during the reaction between the fatty acid alkali compound salt and the magnesium salt, and the dripping speed when the aqueous solution containing the magnesium salt is dripped into the aqueous solution containing the fatty acid alkali compound salt. In addition, for those with a wide particle size distribution, that is, those with a large value of the particle size summary value A, the particle size summary value A can be adjusted in the post-treatment by classification using sieves of 100 mesh, 200 mesh, 330 mesh, etc.
[0029] The microtrack laser diffraction method used here is a method for determining particle size distribution by utilizing scattered light obtained by irradiating particles with laser light. In the present invention, a wet measurement is performed in which a sample is introduced into a circulating organic solvent in which fatty acid magnesium salt particles are not dissolved, such as ethanol or isopropyl alcohol. The particle diameters of the particles to be measured in the present invention are in the range of 0.1 μm to 200 μm, and the value represented by the above formula (1) is taken as the particle size summary value A. In the present invention, the measurement can be performed using, for example, Microtrack MT-3000 manufactured by Nikkiso Co., Ltd.
[0030] The fatty acid magnesium salt particles of the present invention preferably have a volume-based median diameter (D50) of 10.0 to 40.0 μm. Such a particle diameter provides a good feel when used. The fatty acid magnesium salt particles preferably have a median diameter of 13.0 to 35.0 μm, more preferably 15.0 to 25.0 μm. The particle diameter can be measured by a microtrack laser diffraction method in the same manner as the particle size summary value A described above.
[0031] In order to obtain fatty acid magnesium salt particles that satisfy the above-mentioned specific properties, when mixing the magnesium salt-containing aqueous solution and the fatty acid alkali compound salt-containing aqueous solution that are separately prepared by the metathesis reaction, it is preferable to gradually drop the magnesium salt-containing aqueous solution into the fatty acid alkali compound salt-containing aqueous solution. The drop speed is preferably 0.005 to 0.8 mol / min per unit time, more preferably 0.01 to 0.5 mol / min. By mixing at such a drop speed, the exchange reaction between alkali and magnesium can be made to proceed gently, and fatty acid magnesium salt particles having a suitable aspect ratio and thickness can be obtained. When this speed is 0.005 mol / min or more, fatty acid magnesium salt particles having a desired aspect ratio and thickness can be obtained. On the other hand, when the drop speed per unit time is 0.8 mol / min or more or less, the fatty acid magnesium salt particles have a uniform shape, and the particles have the desired aspect ratio and thickness, so that the particle size is not uneven and is good. The unit of "mol / min or more" for the magnesium salt to be added dropwise is the number of moles of magnesium salt to be added dropwise per unit time for 1 mole of fatty acid alkali compound.
[0032] The shape of the fatty acid magnesium salt particles of the present invention is not particularly limited, but from the viewpoint of usability, a plate shape is preferable.
[0033] Cosmetics in which the fatty acid magnesium salt particles of the present invention can be used include skin care cosmetics such as face wash cream, lotion, massage cream, milky lotion, and moisturizing cream; makeup cosmetics such as foundation, eye shadow, eyeliner, lipstick, and blusher; body care cosmetics such as bath additives, sunscreen cream, and deodorant spray; and hair care cosmetics such as shampoo, rinse, hair liquid, and hair color. In addition to the fatty acid magnesium salt particles of the present invention, other known cosmetic raw materials can be used, such as organic pigments, inorganic pigments, fragrances, oils and fats, waxes, hydrocarbons, higher fatty acids, higher alcohols, esters, silicone oils, nonionic, anionic, cationic, amphoteric and other surfactants, moisturizers, ultraviolet absorbers, and antioxidants. EXAMPLES
[0034] The present invention will now be described more specifically with reference to examples and comparative examples.
[0035] [Preparation of magnesium fatty acid (magnesium myristate) salt particles] Example 1 200g of myristic acid (NOF Corp., NAA-142), 1.00g of polyethylene glycol-polypropylene glycol-block ether (NOF Corp., trade name: Pronon #104) and 2500g of water were charged into a 3L separable flask and heated to 80°C. Next, 73.6g of 48% by mass sodium hydroxide aqueous solution was added and stirred at the same temperature (80°C) for 30 minutes to obtain an aqueous solution of sodium myristate. After that, while maintaining the temperature at 80°C, 253.8g of 22% by mass magnesium sulfate aqueous solution was dropped into the aqueous solution of sodium myristate over 40 minutes [dropping rate: 0.013 (mol / min)]. After the dropwise addition, the mixture was kept at 80°C and stirred for 30 minutes to mature. The resulting aqueous solution of magnesium fatty acid salt was allowed to cool to 60°C or less. Thereafter, the mixture was filtered using a suction filter and washed twice with 1000 g of water. The resulting cake was dried at 60° C. using a ventilated tray dryer and crushed in a mill to obtain magnesium myristate particles.
[0036] Example 2 220g of myristic acid (NOF Corp., NAA-142), 1.10g of polyethylene glycol-polypropylene glycol-block ether (NOF Corp., trade name: Pronon #104) and 2400g of water were charged into a 6L separable flask and heated to 85°C. Next, 80.1g of 48% by mass sodium hydroxide aqueous solution was added and stirred at the same temperature (85°C) for 30 minutes to obtain an aqueous solution of sodium myristate. After that, while maintaining the temperature at 85°C, 330.0g of 22% by mass magnesium sulfate aqueous solution was dropped into the aqueous solution of sodium myristate over 60 minutes [dropping rate: 0.010 (mol / min)]. After the dropwise addition, the mixture was kept at 80°C and stirred for 20 minutes to mature. The resulting fatty acid magnesium salt aqueous solution slurry was cooled to 65°C or less. Thereafter, the mixture was filtered using a suction filter and washed six times with 4000 g of water. The resulting cake was dried at 60° C. using a ventilated tray dryer and crushed in a mill to obtain magnesium myristate particles.
[0037] Example 3 A 10L separable flask was charged with 500g of myristic acid (NOF Corp. NAA-142) and 5600g of water, and the temperature was raised to 90°C. Next, 250.0g of 48% by mass sodium hydroxide aqueous solution was added, and the mixture was stirred at the same temperature (90°C) for 1 hour to obtain an aqueous solution of fatty acid alkali compound salt. Then, while maintaining the temperature at 90°C, 750.0g of 22% by mass magnesium sulfate aqueous solution was dropped into the aqueous solution of sodium myristate over 40 minutes [dropping rate: 0.016 (mol / min)]. After the dropwise addition, the mixture was kept at 90°C and stirred for 30 minutes to mature. The resulting aqueous solution of fatty acid magnesium salt was cooled to 65°C or lower. Then, the mixture was filtered with a suction filter, washed with 1000g of water 8 times, and the resulting cake was dried at 60°C using a ventilated tray dryer, and crushed with a mill to obtain magnesium myristate particles.
[0038] Comparative Example 1 200g of myristic acid (NOF Corp., NAA-142), 1.00g of polyethylene glycol-polypropylene glycol-block ether (NOF Corp., trade name: Pronon #104) and 2500g of water were charged into a 3L separable flask and heated to 60°C. Next, 73.6g of 48% by mass sodium hydroxide aqueous solution was added and stirred at the same temperature (60°C) for 30 minutes to obtain an aqueous solution of sodium myristate. After that, while maintaining the temperature at 60°C, 253.8g of 22% by mass magnesium sulfate aqueous solution was added to the aqueous solution of sodium myristate [drop rate: 10.59 (mol / min)]. After the dropwise addition, the mixture was kept at 60°C and stirred for 30 minutes to mature. The resulting fatty acid magnesium salt aqueous solution slurry was filtered using a suction filter and washed twice with 1000 g of water. The resulting cake was dried at 60°C using a ventilated tray dryer and crushed in a mill to obtain magnesium myristate particles.
[0039] Comparative Example 2 A 5L separable flask was charged with 500g of myristic acid (NAA-142 manufactured by NOF Corp.) and 3000g of water, and the temperature was raised to 60°C while stirring, and then 43g of magnesium hydroxide was added at the same temperature over 30 minutes, after which the temperature was raised to 90°C and stirring was continued for 1 hour to obtain a magnesium myristate slurry. This magnesium myristate slurry was cooled to 60°C and filtered using a suction filter, and the resulting cake was dried at 50°C using a ventilated tray dryer and pulverized in a mill to obtain magnesium myristate salt particles.
[0040] Comparative Example 3 200g of myristic acid (NOF Corp., NAA-142), 1.00g of polyethylene glycol-polypropylene glycol-block ether (NOF Corp., trade name: Pronon #104) and 2500g of water were charged into a 3L separable flask and heated to 80°C. Next, 73.6g of 48% by mass sodium hydroxide aqueous solution was added and stirred at the same temperature (80°C) for 30 minutes to obtain an aqueous solution of sodium myristate. After that, while maintaining the temperature at 80°C, 253.8g of 22% by mass magnesium sulfate aqueous solution was dropped into the aqueous solution of sodium myristate over 40 minutes [dropping rate: 0.013 (mol / min)]. After the dropwise addition, the mixture was kept at 80°C and stirred for 30 minutes to mature. The resulting aqueous solution of magnesium fatty acid salt was allowed to cool to 60°C or less. Thereafter, the mixture was filtered using a suction filter and washed twice with 1000 g of water. The resulting cake was dried at 105° C. using a ventilated tray dryer and crushed in a mill to obtain magnesium myristate particles.
[0041] For the magnesium myristate particles of Examples 1 to 3 and Comparative Examples 1 to 3, the median diameter, particle size summary value A [value calculated from 10% cumulative diameter on a volume basis D10 (μm), median diameter on a volume basis D50 (μm), and 90% cumulative diameter on a volume basis D90 (μm)], particle thickness, major axis diameter, and minor axis diameter were measured by the above-mentioned method using the following equipment. The results are shown in Table 1.
[0042] (1) Grain size summary value A, median diameter 2.0 g of sample was placed in a 100 ml glass beaker, and 3 to 5 ml of a nonionic surfactant (e.g., NOF Corp.'s Nonion NS-210) was dropped onto it and mixed with a spatula. Next, 20 ml of purified water was added, and the mixture was dispersed by ultrasonic waves to make a 100 ml volume to be used as the measurement sample. The sample was fed into a particle size distribution measuring device (equipment name: "Microtrac MT-3000", Nikkiso Co., Ltd.) and measured (principle: laser diffraction and scattering method). When a cumulative curve was calculated assuming the total volume of the powder mass to be measured as 100%, the particle sizes at the points where the cumulative curve was 10%, 50%, and 90% were calculated as the 10% diameter (D10), 50% diameter (D50; median diameter), and 90% diameter (D90) (μm), respectively. The particle size summary value A was calculated from the obtained D10, D50, and D90.
[0043] (2) Average particle thickness, major axis diameter, minor axis diameter, aspect ratio, particle index The thickness of the particles was measured using a scanning electron microscope by the following method. After fatty acid magnesium salt particles were attached to double-sided carbon tape, the particle surfaces were coated with platinum particles by vapor deposition, and the sample was observed at an acceleration voltage of 1.0 kV and a magnification of 2000 times, and the thickness of any particle was measured. The thickness, major axis diameter, and minor axis diameter were determined for 10 randomly selected particles. The aspect ratio and particle index were calculated using the following formulas. Particle index = [(major axis diameter (μm) / minor axis diameter (μm)) / average thickness of particles (nm)] × 1000 Aspect ratio = major axis diameter (μm) / minor axis diameter (μm)
[0044] Photographs of the fatty acid magnesium salt particles of Examples 1 and 3 and Comparative Examples 1 to 3 observed with a scanning electron microscope are shown in FIGS.
[0045] [Usability evaluation] The fatty acid magnesium salt particles obtained according to the present invention were evaluated for feel when used, etc., based on the following criteria. The results are shown in Table 1. (Smoothness) Two expert panelists judged the smoothness of the fatty acid magnesium salt particles when applied to the skin as follows, and rated A or B as good smoothness. A: Very smooth B: Smooth C: Not very smooth D: Not smooth (Glossiness) Two expert panelists judged the glossiness of the fatty acid magnesium salt particles on the skin when applied to the skin as follows, and rated the glossiness as good (glossy) in cases A or B. A: Has a strong gloss B: Glossy C: Almost no gloss D: No gloss (Transparency) Two expert panelists judged the sense of transparency when fatty acid magnesium salt particles were applied to the skin as follows, and rated A or B as having good transparency. A: Very transparent B: High transparency C: Slightly less transparent D: Low transparency
[0046] [Table 1]
[0047] As shown in Table 1, the fatty acid magnesium salt particles of Examples 1 to 3, which have aspect ratios and average particle thicknesses within the specific ranges, show good results in all of the categories of smoothness, glossiness, and transparency, and are excellent in usability. In contrast, the fatty acid magnesium salt particles of Comparative Examples 1 to 3, which have aspect ratios and average particle thicknesses that do not satisfy the specific ranges, did not meet the standards in any of the categories of smoothness, glossiness, and transparency.
[0048] <Formulation example: Face powder> Table 2 below shows a formulation example of a face powder containing the fatty acid magnesium salt particles of the present invention.
[0049] [Table 2] [Industrial Applicability]
[0050] The fatty acid magnesium salt particles of the present invention are excellent in usability, such as smoothness, glossiness, and transparency, and are therefore suitable as an additive for cosmetics such as foundations and face powders.
Claims
1. A fatty acid magnesium salt particle having an aspect ratio represented by the following formula (1) of 1.0 or more and 2.0 or less, the fatty acid is selected from lauric acid, myristic acid, palmitic acid and stearic acid; The fatty acid magnesium salt particles have an average thickness of 250 to 600 nm. Aspect ratio=major axis diameter of particle (μm) / minor axis diameter of particle (μm) Equation (1)
2. 2. The fatty acid magnesium salt particles according to claim 1, having a median diameter of 10.0 μm to 40.0 μm.
3. 3. The fatty acid magnesium salt particles according to claim 1, wherein the particle size summary value (A) represented by the following formula (3) satisfies the relationship of A≦2.
5. Grain size summary value A=(D90-D10) / D50 Formula (3) (However, 10.0≦D50≦40.0) D10: 10% cumulative diameter (μm) of fatty acid magnesium salt particles based on volume D50: median diameter (μm) of fatty acid magnesium salt particles on a volume basis D90: 90% cumulative diameter (μm) of fatty acid magnesium salt particles based on volume
4. A cosmetic preparation comprising the fatty acid magnesium salt particles according to any one of claims 1 to 3.
Citation Information
Patent Citations
cosmetic
JP1983049307A
Manufacture of large granule metal soap
JP1984074200A
Colored cosmetic composition
JP1994172128A
Solid powder cosmetic
JP2000169342A
Metallic soap for cosmetic and method for producing the same
JP2007186463A